Delivery of drugs bound to erythrocytes: new avenues for an old intravascular carrier. (July 2015) - Villa, Carlos H; Pan, Daniel C; Zaitsev, Sergei; Cines, Douglas B; Siegel, Donald L; Muzykantov, Vladimir R
For several decades, researchers have used erythrocytes for drug delivery of a wide variety of therapeutics in order to improve their pharmacokinetics, biodistribution, controlled release and pharmacodynamics. Approaches include encapsulation of drugs within erythrocytes, as well as coupling of drugs onto the red cell surface. This review focuses on the latter approach, and examines the delivery of red blood cell (RBC)-surface-bound anti-inflammatory, anti-thrombotic and anti-microbial agents, as well as RBC carriage of nanoparticles. Herein, we discuss the progress that has been made in surface loading approaches, and address in depth the issues relevant to surface loading of RBC, including intrinsic features of erythrocyte membranes, immune considerations, potential surface targets and techniques for the production of affinity ligands.